PENGEMBANGAN PEMBELAJARAN LOMPAT JAUH MELALUI PENDEKATAN BERMAIN PADA PESERTA DIDIK SMA/SMK - Sanio, Antonius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe problems of the research were the learners had difficulty in performing the long jump because the learning activity lack of opportunities to repeat the event. The research and development were aimed at developing a variety of learning through play. The methods in this study used the method of research and development, namely the method of observing the basic stages of design which refers to the development of the Borg & Gall, a simplified according to needs of researchers. The stages of research included the stage of pre-development, namely: The study of literature and relevant research and studied. Development stage: Drafting the concept of the initial product, validation expert, small-scale trials and trials of wide scale up on the final product. The results of research on small scale trials showed the implementation of 5 game concept that is very good (82.86%). The acceptance of the learners on aspects: participation (92%), motivation (86%), and cooperation (97%) each on criteria acceptable and feasible to test on a wide scale. The results of the research on broad-scale trials, there was an increase in the learning outcomes of learners at 18,04%, which means that the development of long jump approach through learning to play on the Senior High School learners viable and can be used in the learning process.Keywords: learning, development of long jump, play